Comparison Between Intrinsic and Extrinsic Motivation of Students in Islamic Religious Education and Moral Values Subjects - Tarsono, Tarsono; Purnama Sari, Yuni; Nugraha, Jaka; Sahira Zandi, Ahmad; Nurjanah, Rita (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
Purpose: To compare students' intrinsic and extrinsic motivation in Islamic Religious Education and Ethics subjects. This research explores how these motivations affect student engagement, academic performance, and long-term interest. This research seeks to understand their impact on learning outcomes by analyzing internal and external motivational factors. The findings will provide insights for developing effective and meaningful learning experiences in these subjects. This study used a quantitative comparative design to compare students' intrinsic and extrinsic motivation in Islamic Religious Education and Cultivation subjects. Data were collected through questionnaires that measured both types of motivation. This study found that students' intrinsic motivation is more dominant than extrinsic motivation in learning Islamic Religious Education and Ethics. The analysis results show that students are more driven by an internal desire to understand the material and apply religious values. Research implications/limitations. The implication of this study is the importance of designing learning that fosters intrinsic motivation, for example, with a value-based approach. The limitations of this study include the limited sample size and the fact that it does not consider social and cultural factors that can affect motivation. Originality/value: This research provides new insights into comparing intrinsic and extrinsic motivation in the context of learning Islamic Religious Education and Ethics, which is expected to help educators design more effective and meaningful learning for students.